Inductive Reasoning in Patients with Paranoid Type Schizophrenia - Mehmet Emrah Karadere; Yasir Safak; Halime Seyma Ozcelik; Emre Demir; Mehmet Hakan Turkcapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The goal of our study is to evaluate the decision making and reasoning of the paranoid type schizophrenic patients, and their confidence in reasoning and perseverance in keeping to their decisions via using Reasoning with Inductive Argument Test (RIAT). Thirty-two delusional patients and 30 healthy volunteers were included in the study. After the diagnostic interview was conducted by SCID-I to the patients who were asked to participate in the study, RIAT test was applied by the interviewer in order to detect the inferential thinking patterns. Apart for the 3rd item out of 11 RIAT items the difference of initial scores are not statistically significant. After both delusional patient group and control groups RIAT items are read, according to ANOVA results of the difference between the belief levels in the result of their initial reasoning and belief level after seeing the alternatives (RIAT belief level before and after), no significant differences were detected for both groups in terms of changes between the belief levels to the RIAT items before and after. According to this study apart from the area of delusions, it can be say that the reasoning of the patients is normal. Our study indicates that when the delusional patients are compared to the control group in terms of jumping to conclusion and modifying their initial beliefs, they are not different when given similarly sufficient amount of data. [JCBPR 2017; 6(2.000): 67-74]